Relationship between Iron Deficiency Anemia (IDA) and Hemoglobin A1C levels in Non- Diabetic Pregnant women in Diwaniyah Teaching Hospital , Diwaniyah city, Iraq - Jabbar, Durar Kamil (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Introduction:. Independent of glycemia, prior research has shown that iron deficiency may increase A1C readings. On the other side, it has been found that (IDA) affects the hemoglobin A1C level; however, the implications are still being studied. The purpose of this study is to look at how pregnant women without diabetes’ HbA1c levels are affected by iron deficiency anemia. Methods: The study comprised 40 of non-diabetic pregnant women who were identified as having IDA and compared to 45 non-diabetic pregnant women group were enrolled to serve as a control group. ranging in age from 20 to 50 years. Hb, RBC, MCV, MCH, MCHC, HbA1c, serum iron, and ferritin were measured. The patient’s data released from Diwaniyah Teaching Hospital , Diwaniyah city, Iraq During five months, and the necessary tests were reviewed by a physician with expertise in this area to guarantee the precision of the strenuous testing. The statistical analysis the data was carried out by using the SPSS19 and Excel 2010 under Windows 8 computer program packages The data were presented as mean ± SD for continuous variables. Group means were compared by t-test.. P value < 0.05 was considered significant. Results: The results show that the mean HbA1c level was significantly increase among IDA group (7.877 μg/dL) compared to control group (5.160 µg/dL) (P<0.05). In the IDA group, mean hemoglobin (Hb), Red Blood Cell count (RBC), serum iron, ferritin, Levels of Hb,mean, corpuscular hemoglobin (MCH), mean corpuscular volume (MCV),mean corpuscular hemoglobin concentration (MCHC) levels were lower than in the non-diabetic healthy women group .Conclusion: A positive correlation between iron deficiency anemia and increased A1C levels was noted in this study. The presence of anemia among pregnant women is very conspicuous in different forms at ages of less than 40 years and during the first trimester of pregnancy, which could create difficulties in identifying uncontrolled diabetes mellitus in the iron-deficient patient. Ferritin and iron status have to be measured during elucidation HbA1c concentrations in diabetes mellitus.